ANALISIS GOVERNANSI KORPORAT DALAM PENCEGAHAN KORUPSI DI BADAN USAHA MILIK NEGARA - Dwi Purwanto; Iin Rosini; Nofryanti Nofryanti (Jurnal Riset Terapan Akuntansi, 2026)
This study aims to analyze the ineffectiveness of corporate governance implementation in preventing corruption within Indonesian State-Owned Enterprises (SOEs). Using a qualitative method and a literature review approach, the research examines books, journals, regulations, guidelines, institutional reports, and electronic sources related to governance practices and corruption control in SOEs. In addition to literature studies, researchers also conducted in-depth interviews to obtain more specific data regarding the implementation of corporate governance in BUMN. The findings indicate that although SOEs have adopted key governance principles—transparency, accountability, responsibility, independence, and fairness—along with several anti-corruption instruments such as gratuity control, whistleblowing systems, conflict-of-interest guidelines, asset-declaration obligations, and codes of conduct, these measures have not been fully effective in reducing corrupt practices. The main obstacles include the limited preventive role of the Gratuity Control Unit, inadequate protection for whistleblowers, weak enforcement of conflict-of-interest sanctions, unclear administrative sanctions for non-compliance with asset reporting, and persistent violations of behavioral standards. These results highlight the need to strengthen governance mechanisms to build a sustainable culture of integrity and restore public trust in SOEs. Keywords: Corporate Governance, Anti-Corruption, State-Owned Enterprises.